Pemakaian E-Commerce untuk Usaha Kecil dan Menengah Guna Meningkatkan Daya Saing - Julisar Julisar; Eka Miranda (Bina Nusantara University, 2013)
One key to the success of Small and Medium Enterprises (SMEs) is the availability of a clear market for the products. Meanwhile, the fundamental weaknesses faced by SMEs in marketing are low market orientation, weakness in a complex and sharp competition and inadequate marketing infrastructure. Faced with an increasingly open market mechanisms and competitive, market control is prerequisite for improving competitiveness. Therefore, expansion of market access with Web-based Information Technology is now needed as a medium for global communication. One thing that gives a competitive advantage in international trade competition is information technology of electronic commerce or e-commerce. This paper shows the important role of e-commerce for SMEs in Indonesia and how to model the development of e-commerce. This paper intends to show the important role of e-commerce for SMEs in Indonesia and how to model the development of ecommerce.